Implementing the boutique of charities in improving the discipline and basic needs of students at Perak Matriculation College / Roshidah Abdul Rahman ... [et al.] - Abdul Rahman, Roshidah; Ahmad, Noor Haslina; Ali, Adzwati; Wan Ahmad Rafaii, Wan Khairunnisa; Mustapa Al Bakri, Marina; Abu Bakar, Amal Zunnairah; Othman Ghani, Nur Diyana (Universiti Teknologi MARA, Kedah, 2019)
The Butik Amal (Charity Boutique) is the social innovation of the category of improvements by Mystique group, at the Perak Matriculation College. Generally the Charity Boutique provide lecturers and staff with the opportunity to contribute students in basic and financial needs. The objective of this study is to see the implementation of the Charity Boutique in improving the discipline and basic needs of students at the Perak Matriculation College. This Charity Boutique has been implemented according to the Procedure of Solution & Proofing through Force Ranking and Design Thinking method of 5W1H and SCAMPER. The survey design was used in this study with a sample of 511 randomly selected in Perak Matriculation College students. The effectiveness of Charity Boutique is measured by using discipline questionnaires and basic needs. The findings show that the level of discipline and the basic needs of students is at high level. This Charity Boutique innovation has the potential to be disseminated in Malaysian higher educational institutions and statutory bodies.